Validity of self-assessment pubertal Tanner stages by realistic color images and Pubertal Development Scale in a longitudinal cohort study - Luo, Jie; Wu, Di; Tian, Yu; Wang, Yujie; Zhang, Qin; He, Zongwei; Wang, Hong; Liu, Qin (Frontiers in Pediatrics, 2024)
To date, the reliability of pubertal development self-assessment tools is questioned, and very few studies have explored the comparison between the self-assessment tools in longitudinal studies. Hence, this study aimed to study the reliability of puberty development self-assessment using Realistic Colour Images (RCI) and Pubertal Development Scale (PDS) in a longitudinal cohort study.Methods: Our longitudinal study recruited 1429 participants (695 boys) aged 5.8-12.2 years old in Chongqing, China. And we conducted two surveys six months apart. Tanner stages were examined by trained medical students at each visit. RCI and the PDS were used to self-assess puberty at each visit. Agreement between Physical Examination (PE) and self-assessment was determined using weighted kappa (wk), accuracy, and Kendall rank correlation.The concordance of puberty self-assessment using RCI at baseline and 1st follow-up in girls and at 1st follow-up in boys was almost perfect, wk > 0.800 (p < 0.001). At baseline, the concordance of genital development self-assessment using RCI was fair in boys, wk = 0.285 (p < 0.001), and the concordance of boys' pubic hair development self-assessment using RCI was poor, wk = 0.311 (95% confidence interval (CI) -0.157 to 0.818). The wk of PDS was less than 0.300, except for the breast development. The reliability and validity of PDS in this study population were low, and the consistency of PDS was not decent.The concordance of RCI is better than that of PDS. The pubertal development self-assessment using RCI is reliable, while the reliability and validity of the PDS are unacceptable. Therefore, RCI is recommended as a reliable pubertal development self-assessment tool to measure pubertal development for large-scale epidemiological investigations and long-term longitudinal studies in China.